Influencia de los factores sociofamiliares en el envejecimiento activo de los usuarios del Centro del Adulto Mayor - Víctor Larco 2021 - Flores Juárez, Heisel Naomi (2023)
The present investigation was carried out with the purpose of analyzing the influence of socio-family factors in the active aging of the elderly of the active users of the Center for the Elderly district of Víctor Larco, province of Trujillo. The sample consisted of 30 active users, during the development of the research methods such as deductive, inductive, statistical and analytical-synthetic were applied, techniques such as interviews and surveys were also used, which were presented through instruments such as the interview guide, the interview record and the survey questionnaire, which were applied to the elderly during the remote modality in the Covid 19 pandemic, which qualitative and quantitative data were collected allowing the analytical understanding of the indicators and its variables. Active aging in older adults and its relationship with social and family factors has given us a positive influence, taking into account aspects such as participation in society, communication, family integration and support. familiar with CAM users, thus contributing to the quality of life of the elderly, counteracting loneliness and depression at this stage of their lives.